Department of Agricultural Extension Don Bosco college of Agriculture, Sulcorna Quepem Goa - Ravindran, Archana; John, Jenny Ann; Jacob, Sanu (Journal of Postharvest Technology, 2021)
Banana inflorescence is an underutilised agricultural by-product, though rich in therapeutic properties. Although valued for its fibre content, consumption  is restricted due to the tedious preparation procedures involved. Moreover, it is a highly perishable product and browning is the major problem associated  with processing. Developing a packaged, shelf-stable, ready-to cook product from the inflorescence would offer consumers a convenient, highly nutritious  option. This will also reduce agricultural wastage and improve the economic status of farmers. Our study aimed at storage studies of processed  inflorescence in a suitable packaging material for a minimum period of 60 days and its value addition. Nutritional and functional properties were also  analysed. Shelf life study indicated that the product packed in metallised polyester-polyethylene pouches was microbiologically safe at every stage of  storage and no peroxides and free fatty acids were formed. Cutlet made out of dehydrated and stored inflorescence were well accepted. Methanolic  extract of dried inflorescence showed good antioxidant activity. Antimicrobial activity was appreciable and it had fairly good anti-diabetic activity too.  Results obtained were promising and revealed that well packaged inflorescence could be stored at room temperature for at least a period of two months  without affecting nutritional and sensory qualities.
Keywords: Banana inflorescence; storage studies; nutritional properties; antioxidant; anti-diabetic; antimicrobial